2012
DOI: 10.1039/c2pp05360h
|View full text |Cite
|
Sign up to set email alerts
|

The donor–acceptor biphenyl platform: A versatile chromophore for the engineering of highly efficient two-photon sensitive photoremovable protecting groups

Abstract: Different photoremovable protecting groups in the o-nitrobenzyl, phenacyl, and 2-(o-nitrophenyl)propyl series with a donor-acceptor biphenyl backbone, known to display excellent two-photon absorption cross-sections, were investigated in order to develop efficient two-photon sensitive photoremovable protecting groups. The 2-(o-nitrophenyl)propyl series was a more versatile platform to increase the two-photon sensitivity of photoremovable protecting groups, leading to the p-alkoxy and p-bisalkylamino-4-nitro-[1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 38 publications
3
43
0
3
Order By: Relevance
“…HPLC analysis showed no hydrolysis by the end of the second day of experiments. These data are consistent with previous reports of similar caged compounds [24, 36] . Finally, at 37°C we found that 2 showed 2.7% hydrolysis after 4 h and 15% after 24 hours (Supplemental Figure 1).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…HPLC analysis showed no hydrolysis by the end of the second day of experiments. These data are consistent with previous reports of similar caged compounds [24, 36] . Finally, at 37°C we found that 2 showed 2.7% hydrolysis after 4 h and 15% after 24 hours (Supplemental Figure 1).…”
Section: Resultssupporting
confidence: 94%
“…Taken together these data suggest that about 30% of the uncaging leads to a product that “hijacks” glutamate release. Goeldner and co-workers have reported similar results with some of their NPP-caged Glu compounds [24, 36] .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…237 This has also been recently demonstrated by Goeldner and co-workers, who studied the photochemical properties of biphenyl-containing photoremovable protecting groups possessing the o -nitrobenzyl, phenacyl, and 2-( o -nitrophenyl)propyl functionalities. 238 …”
Section: Nitroaryl Groupsmentioning
confidence: 99%
“…This large number of engineering constraints has led to the introduction of new types of photolabile protecting groups. Present challenges in the field of caging groups concern: improving the uncaging action cross sections with one- and two-photon absorption[129, 130];driving the uncaging reaction with absorption in the visible range[129, 131135]quantifying the amount of uncaging (e.g. by means of fluorescence reporting)[136141];…”
Section: Photo-activable Molecules For the Control Of Physiological Pmentioning
confidence: 99%